2003
DOI: 10.1590/s0021-75572003000600013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de sorotipos e resistência antimicrobiana de cepas invasivas do Streptococcus pneumoniae

Abstract: Objective: To determine the prevalence of serotypes and antimicrobial susceptibility of invasive strains of Streptococcus pneumoniae and to discuss the implications of these findings for vaccine formulation. Method:Strains of Streptococcus pneumoniae obtained from normally sterile fluids from patients admitted with invasive diseases were isolated and identified at the Hospital de Clínicas, Universidade Federal de Uberlândia, state of Minas Gerais, and forwarded to Instituto Adolfo Lutz, state of São Paulo, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
18

Year Published

2005
2005
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 24 publications
0
15
1
18
Order By: Relevance
“…8,4,[10][11][12] Of this study, seven (54%) of the 13 children less than 2 years old had suffered IPD due to SpNSPn. It is possible that this high level of penicillin resistance is partially due to the fact that HIV+ patients are often given antimicrobial treatment.…”
Section: %mentioning
confidence: 72%
See 1 more Smart Citation
“…8,4,[10][11][12] Of this study, seven (54%) of the 13 children less than 2 years old had suffered IPD due to SpNSPn. It is possible that this high level of penicillin resistance is partially due to the fact that HIV+ patients are often given antimicrobial treatment.…”
Section: %mentioning
confidence: 72%
“…The majority of these refer to colonization of the airways by Sp, since the difficulties in isolating the bacteria from cultures from people with pneumonia are well known. 4,[9][10][11][12][13] The only study published in Brazil on Sp serotypes identified from HIV+ children demonstrated that nasopharyngeal colonization of 112 children was no greater than that described in the literature for healthy children. 3 In our study, serotype 14 was the most frequent (four cases) and was also the serotype that exhibited greatest resistance to penicillin, which confirms data published in Brazilian literature.…”
Section: Resultsmentioning
confidence: 93%
“…8,9 As the STs most frequently isolated from children with invasive and non-invasive diseases are the ones that present the greatest clonal variation, it is essential to develop new vaccines for preventing pneumococcal diseases. 8,9 At present, ST 19 A is the one that causes the greatest concern, not only because of being frequently isolated from vaccinated children that present with IPD in the USA, but also due to the increase in the rate of resistance to antimicrobial agents. 8,9,43,44 …”
Section: Status Of Ipd In Brazil and The Potential Impact Of Pnc7 Vacmentioning
confidence: 99%
“…8,9 At present, ST 19 A is the one that causes the greatest concern, not only because of being frequently isolated from vaccinated children that present with IPD in the USA, but also due to the increase in the rate of resistance to antimicrobial agents. 8,9,43,44 …”
Section: Status Of Ipd In Brazil and The Potential Impact Of Pnc7 Vacmentioning
confidence: 99%
See 1 more Smart Citation